Trial of Fingolimod versus Interferon Beta-1a in Pediatric Multiple Sclerosis - Chitnis, Tanuja; Arnold, Douglas L; Banwell, Brenda; Brück, Wolfgang; Ghezzi, Angelo; Giovannoni, Gavin; Greenberg, Benjamin; Krupp, Lauren; Rostásy, Kevin; Tardieu, Marc; Waubant, Emmanuelle; Wolinsky, Jerry S; et al. (The New England journal of medicine, 2018)
In 215 patients with a median age of 16 years, fingolimod was superior to interferon beta-1a in reducing relapses of multiple sclerosis and the accumulation of new lesions on MRI over a 2-year period. Seizures occurred in 5.6% of patients in the fingolimod group.